2022
DOI: 10.3389/fnmol.2022.1031989
|View full text |Cite
|
Sign up to set email alerts
|

Kölliker’s organ-supporting cells and cochlear auditory development

Abstract: The Kölliker’s organ is a transient cellular cluster structure in the development of the mammalian cochlea. It gradually degenerates from embryonic columnar cells to cuboidal cells in the internal sulcus at postnatal day 12 (P12)–P14, with the cochlea maturing when the degeneration of supporting cells in the Kölliker’s organ is complete, which is distinct from humans because it disappears at birth already. The supporting cells in the Kölliker’s organ play a key role during this critical period of auditory deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 153 publications
0
8
0
Order By: Relevance
“…In the auditory system of altricial mammals, intrinsically spontaneous calcium (Ca 2+ ) waves in the cochleae are prominently present before the ear canal opening at approximately postnatal day 12 (P12) ,, but diminish immediately after the onset of external sound-driven activity. ,, Two candidate mechanisms have been proposed to account for the spontaneous Ca 2+ waves in the developing cochlea. One theory is that the IHCs fire spontaneous Ca 2+ spikes. The efferent neurotransmitter acetylcholine fine-tunes the IHC’s resting membrane potential by activating the acetylcholine receptors of IHCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the auditory system of altricial mammals, intrinsically spontaneous calcium (Ca 2+ ) waves in the cochleae are prominently present before the ear canal opening at approximately postnatal day 12 (P12) ,, but diminish immediately after the onset of external sound-driven activity. ,, Two candidate mechanisms have been proposed to account for the spontaneous Ca 2+ waves in the developing cochlea. One theory is that the IHCs fire spontaneous Ca 2+ spikes. The efferent neurotransmitter acetylcholine fine-tunes the IHC’s resting membrane potential by activating the acetylcholine receptors of IHCs.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In immature sensory systems before experience, such as visual and auditory stimuli, these activities are considered indispensable for instructing the early development of sense and sensibility within a critical period. 24−26 In the auditory system of altricial mammals, intrinsically spontaneous calcium (Ca 2+ ) waves in the cochleae are prominently present before the ear canal opening at approximately postnatal day 12 (P12) 21,27,28 but diminish immediately after the onset of external sound-driven activity. 4,12,25 Two candidate mechanisms have been proposed to account for the spontaneous Ca 2+ waves in the developing cochlea.…”
Section: Discussionmentioning
confidence: 99%
“…In the middle region, P14-17 mice were sacrificed for the CBX experiments and P15-19 for the octanol experiments. The experiment protocol was based on previous studies [1,6,8].…”
Section: Collection Of Experimental Data From Ca 2+ Imaging Of Dcsmentioning
confidence: 99%
“…In the organ of Corti, hair cells are the primary auditory receptor cells [ 5 ]. They are surrounded by supporting cells, including DCs [ 6 , 7 , 8 ] which provide physical and metabolic support to the outer hair cells (OHCs) [ 6 , 9 ]. In addition, they help maintain ion homeostasis in the endolymph via active K + uptake [ 6 , 10 ], and studies have demonstrated that they exhibit functions like glial cells [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation